The Impact of Workplace Inequality and Discrimination on Individual Development and Organisational Performance: A Case Study of Durban’s Hospitality Sector, South Africa - Dr. Nyamupachari Vareta (The Impact of Workplace Inequality and Discrimination on Individual Development and Organisational Performance: A Case Study of Durban’s Hospitality Sector, South Africa, Edition 1, 2025)
Workplaces now consist of many cultures. This varied work environment allows employers opportunities to generate strategies that value diversity while eliminating workplace disparity and prejudice. This research examines the impact of workplace inequality and discrimination on individual development and organizational performance within the hospitality sector in Durban, South Africa. Using a qualitative approach, the study explores employees’ lived experiences through interviews, observations, and thematic analysis with NVivo software. The interviews were conducted face-to-face, audio-recorded, and transcribed. Findings reveal four major themes—recruitment practices, emotional responses, workplace discrimination, and inequality—underscoring the persistence of systemic racism and exploitation, particularly affecting Black employees, women, and foreign workers. The study highlights the negative repercussions on employee motivation, productivity, and organizational performance. According to the results, (95%) of participants say inequality and discrimination are serious against black people, in the hotel Industry. Most feel apartheid has not yet ended in South Africa. The results also show that (80%) of the participants find no relevance in learning or developing themselves in a toxic environment. Findings reveal four major themes—recruitment practices, emotional responses, workplace discrimination, and inequality—underscoring the persistence of systemic racism and exploitation, particularly affecting Black employees, women, and foreign workers. The study highlights the negative repercussions on employee motivation, productivity, and organizational performance. Workers who are discriminated against suffer from low self-esteem and are traumatised. Emotional impact results in a lack of motivation, demoralisation, depression, etc. The social impact results in stress, poor relationships, and poor productivity. The lack of transparency reduces employee participation and turns them into an organisation’s enemy. Practical recommendations include strengthening diversity management. The government must revisit its position on racism, enforce anti-discrimination policies, and enhance systematic training programs to foster inclusivity. These findings contribute valuable insights for HR managers, trade unions, and policymakers to address workplace disparities in the South African hotel industry.